Enhancing employee performance through structured job training: Evidence from Puskesmas Pademangan, Jakarta - Prisia, Epin; Efkelin, Ria; Mailintina, Yurita (Utan Kayu Publishing, 2024)
This study explores the relationship between job training and employee performance at the Puskesmas of Pademangan District, North Jakarta. The study aims to examine how various components of job training, including training objectives, instructors, and materials, affect employee performance. Using a quantitative approach with a descriptive method, data were collected from 192 Puskesmas employees using a structured questionnaire. The results revealed a significant positive relationship between job training and employee performance. Specifically, employees who rated their training programs as